Synthesis, characterization, and microwave dielectric properties of ZnTiTa2O8 ceramics with ixiolite structure obtained through the aqueous sol–gel process. Issue 6 (July 2015) - Wu, H.T.; Feng, Z.B.; Mei, Q.J.; Guo, J.D.; Hou, F.F.; Li, P.S.; Jiang, X.S.
Abstract: Nano-sized ZnTiTa2 O8 powders with ixiolite structure, with particle sizes ranging from 10 nm to 30 nm, were synthesized by thermal decomposition at 950 °C. The precursors were obtained by aqueous sol–gel and the compacted and sintered ceramics with nearly full density were obtained through subsequent heat treatment. The microstructure and electrical performance were characterized by field emission scanning electron microscopy, x-ray diffraction, and microwave dielectric measurements. All the samples prepared in the range 950–1150 °C exhibit single ixiolite phase and relative density between 87% and 94%. The variation of permittivity and Q ·ƒ value agreed with that of the relative density. Pure ZnTiTa2 O8 ceramic sintered at 1050 °C for 4 h exhibited good microwave dielectric properties with a permittivity of 35.7, Q ·ƒ value of 57, 550 GHz, and the temperature coefficient of resonant frequency of about −24.7 ppm/°C. The relatively low sintering temperature and excellent dielectric properties in the microwave range would make these ceramics promising for applications in electronics.